The Meaning of Pondok-Pesantren - Dasuki, Abd. (Al-Jami'ah: Journal of Islamic Studies, 1975)
Pondok-pesantren, sometimes called pondok or pesantren, also pasantren, literally means the residence of santri, the place where the pupil pursues the religious studies. the word pondok itself, means hut, a rude of small house, hovel, cabin, or dormitory. 1) the term santri refers to the pupil who studies in the pondok-pesantren. In the pondok-pesantren  the santri (pupil or disciple) stays and receives various Islamic teachings, i.e. intellectual, mental, spiritual as well as physical education. This Institution is governed by one or more persons called kyai (the rellgious teacher and venerable man). The kyai is considered as a teacher, guardian, trainer, guide, and helper. The term pondok-pesantren as used in the archipelago, refers to the Islamic educational institution, or religious school, which in Madura is called penyantren, in Pasuruhan (west Java) pondok, in Aceh rangkang meunasah an in Minangkabau surau. To give a general idea of the meaning of pondok-pesantren, it is necessary to refer to the points of view of both foreign and Indonesian scholars.